Comparison of Antioxidant and Compound Content of Herbal Tea as A Functional Drink for Patients With Type 2 Diabetes Mellitus - Nuraeni, Rahmawati; Kurniasih, Nunung (ISTEK, 2024)
Type 2 diabetes mellitus is a metabolic condition characterized by high levels of glucose in the blood. People with Diabetes Mellitus need to regulate blood glucose levels by following a strict medical diet, especially in terms of sugar intake. Herbal plants contain antioxidant compounds that can reduce blood glucose levels. This study generally aims to compare the antioxidant power value and compound content of various types of herbal tea. The method used is a literature study using sources through Science Direct and Google Scholar. The results of the review show that plants that can be used as antioxidants and herbal teas that are useful in preventing type 2 diabetes mellitus from various plants that are used as comparison materials can have potential as antioxidants due to the presence of several secondary metabolite compounds such as flavonoids, tannins, saponins, and alkaloids. 50 Of the plants obtained, those that contain antioxidant activity with the strongest category are soursop leaves (Annona Muricata L.) with an IC value of 9.846 ppm. 50 The antioxidant activity with the weakest category is Ciplukan (Physalis angulata) leaves with an IC value of 812.96 ppm. For a little water content of 1.425% in soursop leaves, which indicates that soursop leaf herbal tea is better consumed by patients with type 2 diabetes mellitus, it has the potential to be used as an alternative functional drink.